From flexing to community engagement and repurchase intention: An Indonesian Muslimah luxury brand approach - Haque, Marissa Grace; Rimadias, Santi; Ernaningsih, Indria (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
Starting from the flexing phenomenon, transforming into an exclusive group emotional bond, ending with the intention to buy back Indonesian luxury fashion products, used as a marketing approach for